THE EFFECTIVENESS OF THINK PAIR SHARE (TPS) TECHNIQUE TO IMPROVE READING COMPREHENSION OF DESCRIPTIVE TEXT FOR THE SEVENTH GRADERS OF SMP NEGERI NUNPO - Thresia Trivict Semiun (MEDIA DIDAKTIKA, 2025)
This research aimed to determine the significant effect of using the Think Pair Share (TPS) technique to improve reading comprehension of descriptive texts for seventh-graders of SMP Negeri Nunpo. This research was pre-experimental. The population of this study was the seventh-grader students of class at SMP Negeri Nunpo, with a total of 53 students. Through cluster random sampling, 25 students were taken as samples. The research instrument was a reading comprehension test for descriptive texts consisting of 25 multiple-choice items. The researcher applied the TPS technique for two meetings. The researcher analyzed students' pre-test and post-test scores on descriptive texts, which consisted of main idea questions, stated detail questions, vocabulary in context questions, reference questions, and purpose questions. The results of this study showed that there was a significant difference between the average pre-test score of 51.04 and the average post-test score of 80.64. Based on the above results, the researcher concludes that the use of the TPS technique significantly improved reading comprehension of descriptive texts for seventh-grader students of class A at SMP Negeri Nunpo.